2019
DOI: 10.3389/fphar.2018.01505
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Phosphoinositide-3 Kinases Induce Resolution of Inflammation in a Gout Model

Abstract: Phosphoinositide-3 kinases (PI3Ks) are central signaling enzymes that are involved in many aspects of immune cell function. PI3Kγ and PI3Kδ are the major isoforms expressed in leukocytes. The role of PI3K isoforms in the resolution of inflammation is still poorly understood. Here, we investigated the contribution of PI3Kγ and PI3Kδ to the resolution of inflammation in a model of gout in mice.Methods and Results: Experiments were performed in wild-type male C57/Bl6 mice. Selective inhibitors of PI3K-γ (AS605240… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In those studies, crystals promoted the phosphorylation of the regulatory subunit p85 (class 1A PI3K) and phosphorylation of AKT in a mechanism dependent on protein kinase C activation . Interestingly, a recent study demonstrated that PI3Kγ and PI3Kδ isoforms were important to keep neutrophil viability in synovial cavity after MSU crystal injection and the blockade of those PI3K activities caused neutrophil apoptosis, stimulating the resolution of acute gout inflammation in mouse . However, the contribution of PI3Kγ isoform for the trigger events in gout arthritis was still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, crystals promoted the phosphorylation of the regulatory subunit p85 (class 1A PI3K) and phosphorylation of AKT in a mechanism dependent on protein kinase C activation . Interestingly, a recent study demonstrated that PI3Kγ and PI3Kδ isoforms were important to keep neutrophil viability in synovial cavity after MSU crystal injection and the blockade of those PI3K activities caused neutrophil apoptosis, stimulating the resolution of acute gout inflammation in mouse . However, the contribution of PI3Kγ isoform for the trigger events in gout arthritis was still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Many natural-product PI3K inhibitors, such as wortmannin, have side effects and poor metabolic stability. [5][6][7] In this work, we focused on a PI3K inhibitor, Pi103, that causes reductions in tumor volume in models of acute myeloid leukemia (AML), [8] lung cancer, [9] and skin cancer but has serious side effects. [5][6][7] In this work, we focused on a PI3K inhibitor, Pi103, that causes reductions in tumor volume in models of acute myeloid leukemia (AML), [8] lung cancer, [9] and skin cancer but has serious side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Rho kinase inhibition prevents nuclear factor kappa B activation and I-kappa B phosphorylation and degradation [31]. Prevention of NFκB activation and reduced levels of IκBα phosphorylation was associated with resolution of inflammation [35,59,79,80]. We used different mouse backgrounds because the models of pleurisy induced by LPS and gout were established in the Balb/C and C57Bl/6, respectively, hence their use.…”
Section: Discussionmentioning
confidence: 99%
“…We used different mouse backgrounds because the models of pleurisy induced by LPS and gout were established in the Balb/C and C57Bl/6, respectively, hence their use. In both systems, there are much data suggesting that both systems share the same pathway for neutrophil recruitment and survival [35,59,79,80]. Thus, the requirement of same pathway in different systems to neutrophil survival highlights the importance of this pathway to inflammation resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation